UPAYA MENINGKATKATKAN PERKEMBANGAN MOTORIK HALUS ANAK USIA DINI MELALUI TEKNIK - Siti Rohmah; Abdul Azis; Fanny Fauzi Hanifuni’am (Tarbiyat al-Aulad: Jurnal Pendidikan Islam Anak Usia Dini, 2018)
In teaching and learning activities, to solve the problems that occur children RA Al-Miftah group A is still lacking in the ability to do activities related to fine motor including drawing, cutting, folding, and coloring. Fingers look stiff in holding pencils, holding scissors and folding, so they don't look eager in completing or doing activities. Often they ask for help from fellow friends and even the teacher to complete the activities given. in the development of fine motor skills. Based on the description of the problem there is a problem identification, this research is focused on efforts to improve the development of fine motor children with collage techniques. The research objectives are 1) to determine the ability of teachers in the Preparation of Daily Learning Implementation Plan (RPPH) to improve fine motor development in group A in RA Al-Miftah Sirnabaya Rajadesa. 2) to determine the implementation of fine motor development to children through collage techniques in group A in RA Al-Miftah Sirnabaya Rajadesa. 3) to determine the increase in children's fine motor development through collage techniques in group A in RA Al-Miftah Sirnabaya Rajadesa, after the use of collage techniques in learning. The results of the study are based on data analysis during the preparation of the daily learning implementation plan (RPPH cycle I reaches an average value of 75.18. Thus, the value of preparing the daily learning implementation plan (RPPH) of 75.18 is quite good. Then in preparing the learning implementation plan daily (RPPH) cycle II average value obtained 90.58. The results of the implementation of 85.55 are classified as very good. The results of the implementation of the cycle II reached an average value of 92.77. Based on these results, the average value of the ability of teachers in teaching 85.55 is classified as very good, then in cycle II the average value obtained is 92.77. Thus, the percentage value of the implementation plan of 90.58 is classified as out of bias. The increase in fine motor development in cycle I reaches an average value of 2 , 8. classified as low, then cycle II scores Improvement of fine motor learning of students reach an average value of 3.75 is classified as high